Design and development of android application of gear design ebook and calculator - Muhamad Hafizuddin, Ismail (2012)
Nowadays, tablet and smart phones are well-known for its brilliant operating system which is Android. Android has made its debut in 2008 to become the world most-widely used smartphone platform. Android offers its own operating system, key applications and middleware. The android applications, APK formatted file is very flexible and in variety of choices, from entertainment to education that provide full control to its users.Geardroid is an Android based application for engineering students to study and understand the gear related topics. Its multimedia features allow the users to study and apply their understanding on gears especially on spur gears. Geardroid combines the sufficient notes, formulas, diagram and calculator to understand the gear study and reduce their burden of bringing heavy books to the class. The students can easily calculate needed items by putting the input into the calculator.This Geardroid, developed in Google App Inventor, should be the best choice of application for engineering students to study on gear.